Azimat Dalam Perspektif Sosial-Budaya, Agama, Dan Spiritual Peradaban Manusia - Samsurizal, Samsurizal; Sadi, Ifteakar Mohammad (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study examines the historical roots of amulet usage and its role in the socio-cultural, religious, and spiritual traditions of human civilizations. Utilizing a qualitative research method with a historical approach, data were collected through literature analysis from various sources, including scholarly articles, books, and online documents. The findings indicate that amulets have been an integral part of people's beliefs and identities since early civilizations, serving as tools for protection and supernatural power. In various religions such as Islam, Hinduism, Buddhism, and Christianity, amulets are often incorporated into religious rituals, albeit with differing perspectives. This research reveals the role of amulets in shaping spiritual and cultural identity, both in the past and in contemporary times. The study contributes to interdisciplinary research in the fields of socio-cultural studies, religion, and the humanities, and broadens the understanding of the function and significance of amulets as universal spiritual symbols